Diagnosis and assessment of dilated cardiomyopathy: a guideline protocol from the British Society of Echocardiography. Issue 2 (June 2017) - Mathew, Thomas; Williams, Lynne; Navaratnam, Govardhan; Rana, Bushra; Wheeler, Richard; Collins, Katherine; Harkness, Allan; Jones, Richard; Knight, Dan; O'Gallagher, Kevin; Oxborough, David; Ring, Liam; et al.
Abstract : Heart failure (HF) is a debilitating and life-threatening condition, with 5-year survival rate lower than breast or prostate cancer. It is the leading cause of hospital admission in over 65s, and these admissions are projected to rise by more than 50% over the next 25 years. Transthoracic echocardiography (TTE) is the first-line step in diagnosis in acute and chronic HF and provides immediate information on chamber volumes, ventricular systolic and diastolic function, wall thickness, valve function and the presence of pericardial effusion, while contributing to information on aetiology. Dilated cardiomyopathy (DCM) is the third most common cause of HF and is the most common cardiomyopathy. It is defined by the presence of left ventricular dilatation and left ventricular systolic dysfunction in the absence of abnormal loading conditions (hypertension and valve disease) or coronary artery disease sufficient to cause global systolic impairment. This document provides a practical approach to diagnosis and assessment of dilated cardiomyopathy that is aimed at the practising sonographer.